Praktik Kebersihan Diri untuk Pencegahan Stunting kepada Remaja Panti Asuhan Aisyiyah di Kubu Raya - Ayuk Novalina; Melly Nirma Syahriani; Naura Tsabita (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The problem become a trend in the world is stunting. Stunting is characterized by short body size for age and low cognitive abilities. Vulnerable group that causes stunting problems is teenagers. Apart from eating habits, personal hygiene practices also influence the incidence of stunting. Poor sanitation practices and poor environmental hygiene make body difficult to absorb nutrients. Prevalence of stunting in Indonesia 2022 is 21.7%, while Indonesia's target in 2024 is 14%. One of preventive efforts to achieve reduction in stunting rates is through educational outreach on personal hygiene practices is expected nor increase knowledge but also change health behavior. Method is used by pre-post test. The target of this activity is teenagers from the 'Aisyiyah orphanage in Pontianak City. The results based on the test showed that there was increase in teenagers' knowledge about personal hygiene practices to prevent stunting in teenagers, from 59 respondents there were 19 respondents who had 32.20% less knowledge before given counseling to 33 people with good knowledge or 55.9% after being given counseling. Conclusion: Counseling about personal hygiene practices to prevent stunting for teenagers can increase teenagers' knowledge and are very important for preparing productive teenagers.